Effect of the coexistence of albumin and H2O2 on the corrosion of biomedical cobalt alloys in physiological saline. Issue 57 (15th October 2019) - Xu, Weichen; Zhang, Binbin; Yang, Lihui; Ni, Qiancheng; Li, Yantao; Yu, Fei
Abstract : Corrosion of biomedical Co alloys were firstly studied in the presence of both albumin and H2 O2 . Abstract : The corrosion of Co–28Cr–6Mo and Co–35Ni–20Cr–10Mo, as biomedical alloys, has been investigated for effects of typical species (albumin and H2 O2 ) in physiological saline, with their coexistence explored for the first time. Electrochemical and long term immersion tests were carried out. It was found that Co alloys were not sensitive to the presence of albumin alone, which slightly promoted anodic dissolution of Co–35Ni–20Cr–10Mo without noticeably affecting Co–28Cr–6Mo and facilitated oxide film dissolution on both alloys. H2 O2 led to a clear drop in corrosion resistance, favouring metal release and surface oxide formation and inducing much thicker but less compact oxide films for both alloys. The coexistence of both species resulted in the worst corrosion resistance and most metal release, while the amount and composition of surface oxide remained at a similar level as in the absence of both. The effect of H2 O2 inducing low compactness of surface oxides should prevail on deciding the poor corrosion protection ability of passive film, while albumin simultaneously promoted dissolution or inhibited formation of oxides due to H2 O2 . Corrosion resistance was consistently lower for Co–35Ni–20Cr–10Mo under each condition, the only alloy where the synergistic effect of both species was clearly demonstrated. This work suggests that the complexity of the environment must be considered for corrosion resistance evaluation of biomedical alloys.